First record of Ambrosiodmus (Hopkins, 1915) (Coleoptera: Curculionidae, Scolytinae) in Europe - Faccoli, Massimo; Frigimelica, Gabriella; Mori, Nicola; Toffolo, Edoardo Petrucco; Vettorazzo, Marco; Simonato, Mauro (Zootaxa, 2009)
In early April 2009, many specimens of Ambrosiodmus (Hopkins, 1915) (Coleoptera: Curculionidae: Scolytinae), a genus new to Europe, were found overwintering in a living horse chestnut tree (Aesculus hippocastanum L.) in the botanic garden of Padova (NE Italy) (45°23’ N, 11° 52’ E). In October 2009, about 80 peach trees growing in an orchard close to Verona (Alpo di Villafranca, NE Italy) (45°22’ N, 10° 55’ E) were found infested by the same insect. In both cases, the insects were infesting the tree sapwood infected by honey fungus (Armillaria mellea (Vahl) Kummer). Moreover, in the first week of October one specimen was collected also in a pheromone trap baited with ipsdienol and ipsenol and set up in the international harbour of Venice (Marghera, 45°27’ N, 12° 15’ E). Subsequent morphological analyses ascribed the collected specimens to the species A. rubricollis (Eichhoff, 1875), an ambrosia beetle of Asian origin. The infested trees were submitted to sanitation felling and burnt. Some infested log was placed in a transparent and ventilated plastic cage, kept under laboratory conditions (21±1 °C, 70% r.h., and L16:D8 photoperiod) waiting for insect emergence. Emerging adults were removed daily, identified and sexed by morphological features. The rearing gave several thousands of adults, with a female:male ratio of about 40:1.